2016
DOI: 10.1017/s1041610216000570
|View full text |Cite
|
Sign up to set email alerts
|

How do staff influence the quality of long-term dementia care and the lives of residents? A systematic review of the evidence

Abstract: Confidence in these indicative links is weakened by a lack of high-quality prospective longitudinal studies focusing on potentially adjustable staff variables, with a bias towards cross-sectional studies including only variables that are fixed or unlikely to change. (Review registration no. PROSPERO 2014:CRD42014015224).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 48 publications
2
28
0
2
Order By: Relevance
“…Reviews have indicated both that higher total staffing levels have been associated with improved quality of care and that there is no clear relationship . When describing quality care, the amount of time that care staff spend with residents is considered highly important by both residents and their family members .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews have indicated both that higher total staffing levels have been associated with improved quality of care and that there is no clear relationship . When describing quality care, the amount of time that care staff spend with residents is considered highly important by both residents and their family members .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has suggested positive associations between staff variables (including training, education, numbers and skills) and quality of care; yet, evidence is lacking in order to clearly determine a staffing mix that optimises quality of life for residents . Studies do suggest however that where staff treat and interact empathically in their care there are better outcomes for residents including behaviour (positive affect) and less decline in functional status …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that nonpharmacological factors, such as aspects of the environment, can help to reduce residents’ symptoms and enhance quality of life. However, achieving an appropriate balance between pharmacological and nonpharmacological therapies depends on the trust that residents have in their caregivers, and it has been shown that when care is empathic and humane, residents demonstrated a positive mood, delayed functional dependence and consumed more food (Anderson, Bird, MacPherson, & Blair, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…이는 입소 노 인의 자율성 및 자기결정권을 보장할 뿐만 아니라 [5] 일상생 활 수행능력의 향상 및 무력감과 우울과 같은 부정적 정서의 감소, 전반적인 삶의 질 향상 [6], 욕창 발생률, 연간 병원 입원 율의 감소 등 [7]의 결과로 보고되었다. 노인요양시설에서 직 접 간호 및 요양서비스를 제공하는 간호사 및 간호보조 인력 의 인간중심케어 수준은 케어의 질과 입소 노인의 삶의 질에 영향을 미치는 것으로 나타났다 [8]. 노인요양시설 [6,8], 직무만족, 자기개발능력, 인 간중심케어에 대한 지식수준 등 [9,10]의 개인적 요인의 영향 을 받는 것으로 나타났다.…”
unclassified
“…노인요양시설에서 직 접 간호 및 요양서비스를 제공하는 간호사 및 간호보조 인력 의 인간중심케어 수준은 케어의 질과 입소 노인의 삶의 질에 영향을 미치는 것으로 나타났다 [8]. 노인요양시설 [6,8], 직무만족, 자기개발능력, 인 간중심케어에 대한 지식수준 등 [9,10]의 개인적 요인의 영향 을 받는 것으로 나타났다. 또한 시설 규모, 직원 대 노인 비율, 상급자의 리더십, 물리적 환경 등 조직적 요인의 영향을 받는 것으로 보고되었다 [11].…”
unclassified